ANALISIS MOTIF MASYARAKAT NON MUSLIM MENJADI NASABAH PEMBIAYAAN PADA BANK PEMBIAYAAN RAKYAT SYARIAH AMANAH INSAN CITA (AIC) CABANG LUBUK PAKAM - Claudio Ramadona; Tuti Anggraini; Mawaddah Irham (WELFARE: Journal of Islamic Economics and Finance, 2023)
This study aims to find out what the motives of non-Muslims are to become financing customers at the AmanahInsan Cita (AIC) Sharia People's Financing Bank, Lubuk Pakam branch. This type of research uses aqualitative descriptive approach. The conclusions of this study in brief are: the motives of non-Muslimcommunities to become financing customers of BPRS AIC Lubuk Pakam Branch are based on promotions,products offered by the bank, transparency, and places or locations between people's residences that are easy toreach to the Bank. Things that must be considered and increased by the Bank to increase customers include:increasing fund distribution activities in the form of financing for the community to run optimally so as toincrease profits and improve the performance of a company. As well as increasing the work ethic of employeesso that under financing supervision it can reduce the level of risk in financing and marketing in the financingproducts contained in the BPRS AIC Lubuk Pakam Branch which are more in demand by the public.